2007
DOI: 10.1152/jn.00249.2007
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects on the Limits and Stability of Long-Term Synaptic Potentiation and Depression in Rat Hippocampal Area CA1

Abstract: Altered hippocampal synaptic plasticity may underlie age-related memory impairment. In acute hippocampal slices from aged (22-24 mo) and young adult (1-12 mo) male Brown Norway rats, extracellular excitatory postsynaptic field potentials were recorded in CA1 stratum radiatum evoked by Schaffer collateral stimulation. We used enhanced Ca(2+) to Mg(2+) ratio and paired-pulse stimulation protocol to induce maximum changes in the synaptic plasticity. Six episodes of theta-burst stimulation (TBS) or nine episodes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 64 publications
7
57
0
Order By: Relevance
“…resonance imaging studies showed shrinking of hippocampal volume by 20% in elderly healthy adults [23]. Presented LTP measurements indicate the ability to induce and maintain synaptic plasticity in middleaged hippocampus in coincidence with finding even in senescent 22-24-m/o rats compared to young 1-12-m/o rats [24]. Pronounced reduction of absolute magnitude of fEPSP as well as fEPSP slope before and after HFS indicates persisting neurotransmission impairment already in the middle-aged rat hippocampus.…”
Section: Discussionsupporting
confidence: 73%
“…resonance imaging studies showed shrinking of hippocampal volume by 20% in elderly healthy adults [23]. Presented LTP measurements indicate the ability to induce and maintain synaptic plasticity in middleaged hippocampus in coincidence with finding even in senescent 22-24-m/o rats compared to young 1-12-m/o rats [24]. Pronounced reduction of absolute magnitude of fEPSP as well as fEPSP slope before and after HFS indicates persisting neurotransmission impairment already in the middle-aged rat hippocampus.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with this, we observed deficits in synaptic function before A␤ deposition that either corrected or stabilized as the animals aged and plaque formation began. Two potential explanations for this finding include a change in the toxic forms of A␤ at this age (Lesné et al, 2008) or an improved ability to compensate with age, perhaps due to age-dependent changes in the molecular mechanisms of LTP (Kumar et al, 2007;Gruart et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…If further exploration of aging and AD changes in synaptic function and plasticity is one of your goals, there are at least two other methodological issues, alluded to above, that deserve further consideration. First, several labs have shown that the Ca 2+ :Mg2+ ratio in recording ACSF can have a marked effect on the induction synaptic plasticity in hippocampal slices 2,10,24,25 . In mammalian CSF, the Ca 2+ :Mg2+ ratio is approximately one (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of LTD is particularly sensitive to subtle changes in ACSF Ca 2+ levels. Our protocol, which uses 2mM Ca 2+ and 2 mM Mg2+, commonly results in LTD for aged, but not young adult animals 2 , while studies using a Ca 2+ :Mg2+ ratio closer to two, have observed robust LTD in adults in the absence of an age difference 2,10 or in conjunction with reduced LTD in aged rats 32 . These observations highlight the need to carefully consider ACSF Ca 2+ and Mg2+ levels when comparing Ca…”
Section: +mentioning
confidence: 95%
See 1 more Smart Citation